Tingkat Kesadaran Masyarakat Kawasan Ekonomi Khusus Mandalika terhadap Pentingnya Pendidikan Anak Usia Dini - Cahyani, Baiq Ria Rizkia; Tahir, Muhammad; Sriwarthini, Ni Luh Putu Nina; Rachmayani, Ika (Diniyah: Jurnal Pendidikan Dasar, 2024)
Early childhood education is currently mandatory for every child. However, high economic demands require parents to involve their children in economic activities around the Mandalika Special Economic Zone. This study aims to assess the level of community awareness regarding early childhood education and to describe efforts to enhance this awareness. Data collection was conducted using observation, questionnaire, and interview. Data were analyzed through stages of data reduction, data presentation, and conclusion. The findings indicate that the community in the Mandalika Special Economic Zone has a moderate level of awareness regarding the importance of early childhood education. Efforts to increase public understanding of the significance of early childhood education can be made through parental involvement via workshops, seminars, and online discussions through platform like WhatsApp Groups. The government needs to provide facilities for these parental activities to raise awareness about the importance of early childhood education.Keywords: Early childhood education, education awareness, mandalika special economic zone